Giving permission for adults to play. - Andrew Walsh (University of Huddersfield Press, 2019)
Play is often seen as inappropriate in adult settings, with social expectations causing adults to frame situations in such a way that we often lack permission to play. Semi-structured interviews with fourteen people who use playful approaches with adults were carried out to explore how they gave this "permission to play" in their contexts. It was seen that they used a range of different ways consistent with the idea of needing to signal a shift in frame, and this range of approaches to giving "permission to play" are grouped and summarized in the article.